Treatment Increasing the Strength of Polymer Materials: Perawatan Meningkatkan Kekuatan Bahan Polimer - Rosilov Mansur Sirgiyevich; Nurullayeva Dilsora Dilshod (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the pivotal role of PE carbonyl groups in light resistance, with a focus on their impact during different stages of aging. Through the application of mechanochemical destruction, hydroperoxides are formed as initiators of photoaging in PE. Our findings reveal the superior effectiveness of hydroperoxides in early aging stages, while the presence of carbonyl groups exerts significant influence in later stages. The results emphasize the dual mechanisms driving photoaging in PE and provide valuable insights for developing strategies to enhance its durability and longevity. Highlights: The presence of carbonyl groups in polyethylene determines its resistance to light. Hydroperoxides formed during mechanochemical destruction initiate photoaging in polyethylene. Carbonyl groups play a significant role in the later stages of polyethylene photoaging. Keywords: Polyethylene, photoaging, carbonyl groups, hydroperoxides, light resistance.